A Morphological Analysis Of Derivational Affixes (Suffix) -Er And -Or In The Jakarta Globe Newspapers November 1-7, 2012 - Azis, Nur Chairul, Drs. Sigit Haryanto, M. Hum, Dra. Dwi Haryanti, M. Hum (2013)
This study deals with the similarities and differences between the usage of suffix -er and -or in Jakarta Globe Newspaper November 1-7,2012, describing the characteristic of suffix -er and -or in Jakarta Globe Newspaper November 1-7,2012. This research paper is conducted by using descriptive qualitative method. The object of the research is The Jakarta Globe Newspaper November 1-7, 2012. Method of data collection is documentation and the steps are reading the newspaper, underlying the word that use suffix -er and -or found in newspaper, classifying and writing the data. The t e chnique of ana lyz ing da t a of thi s r es e a r ch a r e ident i fying the dat a , cl a s s i f ying and de s c r ibe the dat a ba s ed on the s imi l a r i t i e s , di f f e r enc e s and cha r a c t e r i s t i c of dat a . From the result of analysis, it can be drawn some conclusions. Firstly The usage of suffix -er and -or have similarities in the function grammar category. When the word category likes noun, verb and adjective are followed by suffix -er and -or, the grammatical category will change into noun category, and the differences between suffix -er and -or are related to the characteristic of each suffix. Secondly, the characteristic of suffix -er. The suffix following the verb morpheme with final letter vowel [e]: 38 data, consonant [y]: 5 data, [t]: 10 data, [d]: 12, [n]: 6 data, [p]: 5 data, [w]: 5 data, [k]: 10 data, [m]: 2 data, [h]: 5 data, [l]: 5 data, [g]: 1 datum, the suffix following noun morpheme with final letter vowel [e]: 4 data, consonant [y]: 3 data, [t]: 1 datum, [n]: 4 data, [k]: 2 data, [m]: 4 data, [l]: 2 data, [f]: 1 datum, the suffix following the adjective morpheme with final letter vowel [e]: 4 data, consonant [d]: 2 data, [n]: 4 data. Then the characteristic of suffix -or: the suffix following the verb morpheme with final letter vowel [e]: 26 data, consonant [t]: 10 data, [n]: 1 datum, [s]: 2 data, [d]: 1 datum, the suffix following noun morpheme with final letter consonant [t]: 2 data, [s]: 1 datum, the suffix following adjective morpheme with final letter consonant [t]: 1 datum.